Vibrationally cold CO2+ in intense ultrashort laser pulses - McKenna, J.; Sayler, A. M.; Anis, F.; Johnson, Nora G.; Gaire, B.; Lev, U.; Zohrabi, M. A.; Carnes, K. D.; Esry, B. D.; Ben-Itzhak, I. (My University, 2010)
By virtue of the short lifetime of excited states, we have performed three-dimensional (3D) momentum imaging on the fragments from an electronically and vibrationally cold metastable CO2+ beam following irradiation by intense ultrashort laser pulses. This unique target can be described as a two-channel system, since most low-lying electronic states are not accessible by dipole transitions due to their spin state. Laser excitation between the ground X3Π v=0 state and the excited 3Σ− state leads to bond softening and above-threshold dissociation, with peaks in kinetic energy release spaced by the photon energy and interesting angular distributions that peak perpendicular to the laser field. These results are compared with our solutions of the 3D time-dependent Schrödinger equation.